2020
DOI: 10.21203/rs.3.rs-54219/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mild traumatic brain injury is associated with effect of inflammation on structural changes of default mode network in those developing chronic pain

Abstract: Background:Mild traumatic brain injury (mTBI) has a higher prevalence (more than 50%) of developing chronic posttraumatic headache (CPTH) compared with moderate or severe TBI. However, the underlying neural mechanism for CPTH remains unclear. This study aimed to investigate the inflammation level and cortical volume changes in patients with acute PTH (APTH) and further examine their potential in identifying patients who finally developed CPTH at follow-up.Methods:77 mTBI patients initially underwent neuropsych… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Given the a priori finding of an association, the Bonferroni adjustment may have been too conservative. 46 Overall, this finding of an association between the neuropathic headaches and abnormal enlargement of the posterior cingulate cortex provided moderately good support for the previous similar finding by Niu et al 69 As those authors pointed out, there is a higher prevalence of chronic posttraumatic headache in mild TBI than in moderate or severe TBI, which is surprising because most symptoms are less severe in mild TBI. Similarly, abnormal enlargement appears to occur more often in mild TBI, which is surprising because most volume abnormalities have been reported to occur less often in mild TBI.…”
Section: Theoretical Importance Of Abnormal Enlargementsupporting
confidence: 79%
See 1 more Smart Citation
“…Given the a priori finding of an association, the Bonferroni adjustment may have been too conservative. 46 Overall, this finding of an association between the neuropathic headaches and abnormal enlargement of the posterior cingulate cortex provided moderately good support for the previous similar finding by Niu et al 69 As those authors pointed out, there is a higher prevalence of chronic posttraumatic headache in mild TBI than in moderate or severe TBI, which is surprising because most symptoms are less severe in mild TBI. Similarly, abnormal enlargement appears to occur more often in mild TBI, which is surprising because most volume abnormalities have been reported to occur less often in mild TBI.…”
Section: Theoretical Importance Of Abnormal Enlargementsupporting
confidence: 79%
“…Empirical evidence for this idea comes from a study of a group of patients with mild TBI, which found that abnormal enlargement of the anterior and posterior cingulate regions was associated with posttraumatic headache and a serum marker of neuroinflammation. 69 In a post hoc attempt to explore this possibility, we attempted to partially replicate their findings.…”
Section: Theoretical Importance Of Abnormal Enlargementmentioning
confidence: 99%